Strategi Pemberitaan Covid-19 Pada Media Cetak Harian Republika - A. Rani Usman; Fakhruddin (Sadida Islamic Communications and Media Studies, 2022)
This article discusses the important role related to the news of the corona virus in the Republika media, this study uses a descriptive method. The data was obtained from journalists and editors related to the news in the Republika Daily. From the results of this study, it was found that news about the corona virus in an Islamic perspective was conveyed accurately, honestly and openly to the public who read Republika Daily.